Teacher Professional Learning in Pursuit of the Common Good: A Discussion of the Role of demonstration schools in Teacher Education - Loughland, Tony (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
The Federal Government in Australia has recently established Centres for Excellence in Teacher Education. These Centres represent a power shift towards schools in teacher education and away from centralised bureaucracies and university faculties of education. Given this shift, it is interesting to examine other historical and current school-based models of teacher education, specifically demonstration schools in the United Kingdom, United States, and Australia and professional development schools in the United States. This paper discusses both models with a detailed case study of the operation of one demonstration school in Sydney, Australia. The discussion and case study reinforces the lessons of the historical models that initiatives in this area need long-term support so that they can develop the momentum necessary to achieve the long-term cultural change required.